METHOD DEVELOPMENT AND VALIDATION OF ULTRAVIOLET-VISIBLE SPECTROSCOPIC METHOD FOR THE ESTIMATION OF HEPATITIS-C DRUGS - DACLATASVIR AND SOFOSBUVIR IN ACTIVE PHARMACEUTICAL INGREDIENT FORM - Chakravarthy V, Ashok; Bbv, Sailaja; A, Praveen Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the present work is to develop a simple, efficient, and reproducible spectrophotometric method for the quantitative estimation of hepatitis-C drugs - Daclatasvir and Sofosbuvir in its active pharmaceutical ingredient (API) form. Methods: The developed ultraviolet spectrophotometric method for the quantitative estimation of hepatitis-C drugs - Daclatasvir and Sofosbuvir is based on measurement of absorption at a wavelength maximum (Î»max) of 317 and 261 nm using methanol as solvent. Results: The method was validated in terms of specificity, precision, linearity, accuracy, and robustness as per the ICH guidelines. The method was found to be linear in the range of 50-150% for Daclatasvir and in the range of 43-143% for Sofosbuvir. The percentage recovery values were in the range of 99.4-100.6% for Daclatasvir and in the range of 99.7-100.6% for Sofosbuvir at different concentration levels. Relative standard deviation for precision and intermediate precision results were found to be <2%. The correlation coefficient value observed for Daclatasvir and Sofosbuvir drug substances was not <0.99, 0.99, respectively. Results obtained from the validation experiments prove that the developed method is quantified for the estimation of Daclatasvir and Sofosbuvir drug substances. Conclusion: The developed method can be successfully applied for routine analysis, quality control analysis, and also suitable for stability analysis of Daclatasvir and Sofosbuvir in API form as per the regulatory requirements. Keywords: Daclatasvir, Sofosbuvir, Method development, Validation, Ultraviolet-visible spectrophotometry.